Development of construction project cost budget application using rapid application development method - Denny Jean Cross Sihombing (Institute of Computer Science (IOCS), 2023)
This research aims to develop a Construction Project Cost Budget Plan application using the Rapid Application Development (RAD) approach. Through prototype evaluation, the app was tested by 150 critical stakeholders in the construction industry, including project managers, estimators, and additional stakeholders. The evaluation results show that the app integrates critical features such as budget calculation, real-time monitoring, customizable reporting, resource management, project planning, team collaboration, cloud integration, and budget data analysis. This research encourages further development and broader stakeholder participation in the next stage of development. This research contributes to developing innovative applications that can help the construction industry face the challenges of complexity, improve the efficiency of project budget management, and provide relevant and sustainable solutions. In addition, this research provides an opportunity to explore the potential use of artificial intelligence (AI)-based technology and blockchain technology in construction project management.